Finite Element Analysis of Floating, Production, Storage and Offloading (FPSO) Vessel Subjected to Sudden Crash (Impact) Load - Olalekan H. I., Oluwole O.O. & Odunfa K.M (Covenant Journal of Engineering Technology, 2018)
The need for deep-water development and continuous exploitation of depleting shallow water reserves has spawned new forms of offshore structures like FPSO (Floating, Processing, Storage and Offloading) vessel for production and storage of oil or gas. Many offshore structures have been designed to cater for these needs but FPSO due to its storage capacity and ease of installation is suitable for smaller fields which can be depleted quickly and avoids the need for installing permanent and expensive pipelines. However, for continuous production and offloading of oil, DP shuttle tanker which has flexibility of loading and transporting oil to any destination is required since FPSO would not hold crude products for a longer period. Thus, tandem offloading operation from FPSO to DP shuttle tanker is essential. This work aimed at studying the effect of crash (impact) load on FPSO in tandem offloading operation was achieved by modeling an FPSO using SolidWorks then subjected to impact/collision at different velocities of DP shuttle tanker which ranges between 0.6m/s to 200m/s. ANSYS Explicit Dynamics was used to analyze parameters like deformation/displacement, stress and equivalent elastic strain under the impact (collision) loading. The results obtained from the simulation reveled that at DP shuttle tanker velocities 5m/s and 20m/s the crash load did not reached the damage point on both FPSO and DP shuttle tanker. At velocities above 20m/s there is a great damage after collision. In addition, as the velocity of DP shuttle tanker increases, the values of those parameters also increase. This implies that at low velocity of DP shuttle tanker in tandem offloading operation, the risk of damage after impact/collision is lesser and at velocity greater than 20m/s there is tendency of heavy damage after collision resulting to stern damage on FPSO and consequent penetration and flooding in the machine room.